Modulation of Cell Sialoglycophenotype: A Stylish Mechanism Adopted by Trypanosoma cruzi to Ensure Its Persistence in the Infected Host - Freire-de-Lima, Leonardo; Fonseca, Leonardo M. da; da Silva, Vanessa A.; da Costa, Kelli M.; Morrot, Alexandre; Freire-de-Lima, Célio G.; Previato, Jose O.; Mendonça-Previato, Lucia (Frontiers in Microbiology, 2016)
Trypanosoma cruzi, the etiological agent of Chagas disease exhibits multiple mechanisms to guarantee its establishment and persistence in the infected host. It has been well demonstrated that T. cruzi is not able to synthesize sialic acids (Sia). To acquire the monosaccharide, the parasite makes use of a multifunctional enzyme called trans-sialidase (Tc-TS). Since this enzyme has no analogous in the vertebrate host, it has been used as a target in drug therapy development. Tc-TS preferentially catalyzes the transfer of Sia from the host glycoconjugates to the terminal β-galactopyranosyl residues of mucin-like molecules present on the parasite's cell surface. Alternatively, the enzyme can sialylate/re-sialylate glycoconjugates expressed on the surface of host cells. Since its discovery, several studies have shown that T. cruzi employs the Tc-TS activity to modulate the host cell sialoglycophenotype, thus favoring its perpetuation in the infected vertebrate. In this review, we summarize the dynamic of host/parasite sialylglycophenotype modulation, highlighting its role in the subversion of host immune response in order to promote the establishment of persistent chronic infection.